Bacterial DNA activates cell mediated immune response and nitric oxide overproduction in peritoneal macrophages from patients with cirrhosis and ascites. Issue 6 (11th May 2004) - Francés, R; Muñoz, C; Zapater, P; Uceda, F; Gascón, I; Pascual, S; Pérez-Mateo, M; Such, J
Abstract : Background and aims: Translocation of intestinal bacteria to ascitic fluid is probably the first step in the development of episodes of spontaneous bacterial peritonitis in patients with cirrhosis. We have recently reported the detection of bacterial DNA in blood and ascitic fluid from patients with advanced cirrhosis, what we consider as molecular evidence of bacterial translocation. Several studies have shown the immunogenic role of bacterial DNA in vitro, and we hypothesised that the presence of bacterial DNA could activate the type I immune response in peritoneal macrophages from these patients, leading to greater cytokine synthesis (interleukin (IL)-2 and IL-12, tumour necrosis factor α, and interferon γ) and effector molecules such as nitric oxide. Methods: Peritoneal macrophages obtained from patients with cirrhosis and culture negative non-neutrocytic ascitic fluid were collected and characterised by flow cytometry. Inducible nitric oxide synthase, nitric oxide levels, and cytokine production were measured by immunoenzymometric assays in basal and harvested conditions according to the presence/absence of bacterial DNA. Results: The ability of peritoneal macrophages to synthesise nitric oxide and levels of all cytokines were significantly increased in patients with bacterial DNA. There was a positive correlation between inducible nitric oxide synthase and nitric oxide levels. Conclusions: The presence of bacterial DNA in patients with decompensated cirrhosis is associated with marked activation of peritoneal macrophages, as evidenced by nitric oxide synthesising ability, together with enhanced cytokine production.